Surgically treated Hoffa Fractures with poor long-term functional results - (:unkn) unknown (ELSEVIER SCI LTD, 2018)
Introduction: Hoffa fractures are rare injuries and usually involve the lateral condyle. There are few published studies of large series of isolated coronal plane fractures of the femoral condyle. The aim of the study to determine the long-term functional outcomes and complications in surgically treated Hoffa fractures. Patients and methods: A retrospective review was made of 13 consecutive patients who were treated surgically for an isolated coronal plane fracture of the distal femur posterior condyle. The patients were evaluated with physical examination, PA and lateral radiographs and CT at the final follow-up examination. Functional outcome was evaluated with the OXFORD knee scoring system and Knee Society Score (KSS). Pain at rest and in activity was assessed using a Visual Analog Scale (VAS). Results: The patients comprised 11 males and 2 females with an average age at surgery of 27.5 years. The mean follow-up period was 93 months (range, 62-134 months). Mean time to fracture healing was 10 weeks (range, 8-12 weeks). The mean ROM was determined as 110 degrees, mean KSS 78,4 and mean Oxford knee score 38,2. The mean KSS was 66,5 for medial Hoffa fracture patients and it was 83,8 for lateral Hoffa fracture patients. The mean Oxford knee score was 33,2 for medial Hoffa fracture patients and it was 40,4 for lateral Hoffa fracture patients. The mean VAS at rest and in activity was 1,1 and 2,9, respectively. Osteoarthritis was seen in 7 (54%) patients and avascular necrosis in 2 (15.4%). Varus instability was determined in 1 patient and valgus instability in 1 patient. Conclusion: Hoffa fractures may easily be overlooked if the radiological examination is not made carefully. Screw fixation was seen to provide enough biomechanical stability until the fracture healed. Arthrosis is a frequent long-term complication which worsens the functional results. Medial Hoffa fractures tend to have worse functional results than lateral Hoffa fractures. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Hoffa fractures; Surgery; Long-term results; DISTAL FEMORAL CONDYLE; CORONAL FRACTURES; FEMUR; ASSOCIATION; MANAGEMENT; SCREWS; PLATE